Pathophysiological and Clinical Aspects of Chronic Rhinosinusitis: Current Concepts - Vlaminck, Stephan; Acke, Frederic; Scadding, Glenis K.; Lambrecht, Bart N.; Gevaert, Philippe (Frontiers in Allergy, 2021)
Adult chronic rhinosinusitis (CRS) is a chronic inflammation of the mucosa of the nose and paranasal sinuses. According to the latest EPOS guidelines CRS should be regarded as primary or secondary with distinction between diffuse and localized disease. Further pathophysiologic research identified different inflammatory patterns leading to the term “endotyping of CRS.” The primary focus of endotyping is to define a dominant inflammatory type allowing for better orientation of therapy. The current approach proposes the differentiation between type 2 (eosinophilic) and non-type 2 inflammatory responses. In this review pathophysiological concepts of CRS will be discussed, focusing on the different inflammatory endotypes of T cells with special attention to the eosinophilic type 2 inflammatory response. The contribution of innate and adaptive immune system responses is presented. The possibility of endotyping based on sinonasal secretions sampling is brought to attention because it is indicative of corticosteroid responsiveness and available to most ENT surgeons. Furthermore, the clinical aspects of the three distinct phenotypes are analyzed in view of their characteristics, the related endoscopic findings, typical radiological imaging, histopathology findings, their relation toward allergy and obvious therapeutical implications. This overview will enable clinicians to relate pathophysiological patterns with clinical observations by explaining the different inflammatory mechanisms, hence providing a better understanding of therapy.